What insiders know about future earnings and how they use it: Evidence from insider trades - Ke, Bin; Huddart, Steven; Petroni, Kathy (Journal of Accounting and Economics, 2003)
This paper provides evidence that insiders possess, and trade upon, knowledge of specific and economically significant forthcoming accounting disclosures as long as 2 years prior to the disclosure. Stock sales by insiders increase three to nine quarters prior to a break in a string of consecutive increases in quarterly earnings. Insider stock sales are greater for growth firms, before a longer period of declining earnings, and when the earnings decline at the break is greater. Consistent with avoiding an established legal jeopardy, there is little abnormal selling in the two quarters immediately prior to the break.